CONSENSUS IN THE CRIMINAL PROCESS: THE EFFECTIVE PARTICIPATION OF THE VICTIM IN THE NON-PERSECUTION AGREEMENT - Rocha Valença Figueiredo, Isabelle (2021)
This article aimed to analyze the construction of consensus in the criminal process, through article 28-A of the Brazilian Penal Procedure Code. The emphasis was placed on the victim's participation in the construction of the non-criminal prosecution agreement. Also noteworthy are the actions of the Public Ministry. This in an attempt to bring the victim closer to the process and the legislative measures aimed at this procedural figure. The bibliographic referential methodology was adopted in the research, using books, articles and works that deal with the subject studied and Brazilian legislation. In this regard, the general aspects of consensus in the criminal process were initially studied, based on a reanalysis of the structure of the Brazilian criminal process in an attempt to explore its conceptualization and its restorative aspect. In the second part of the study, an analysis of article 28-A of the Code of Criminal Procedure was carried out, by scrutinizing the non-criminal prosecution agreement, passing through the existence, validity and effectiveness plans. Subsequently, the object of the agreement was analyzed, in order to arrive at reparation of the damage caused to the victim. From there, the victim's means of participation in building consensus were exposed. Thus, the highlight was the effective actions to be taken by members of the Public Ministry in bringing the victim to the construction of the agreement.